Mining Goes Digital Proceedings of the 39th international Symposium 'Application of Computers and Operations Research in the Mineral Industry' (APCOM 2019), Wroclaw, Poland, 4-6 June 2019 - Mueller, Christoph; Assibey-Bonsu, Winfred; Baafi, Ernest; Dauber, Christoph; Doran, Chris; Jerzy Jaszczuk, Marek; Nagovitsyn, Oleg (Proceedings in Earth and geosciences, 2019)
The abbreviation "APCOM" stands for "Applications for Computers and Operations Research in the Minerals Industry". When the conference started in 1964, it was an informal meeting of scientists from different universities in the USA together with the "Society of Mining Engineers" (SME) of the United States. During the years the APCOM conference was performed in a mostly bi-annual rhythm. Up to today APCOM maintained its original logo formed around a punch card clearly remembering the historic origin of the conference from the times prior to the revolution caused by the era of semiconductors. In the beginning, APCOM focused on the optimization of geostatistics and resource estimation and a number of methods used in these fields were initially presented and discussed on APCOM conferences. This field still today is an important part of any APCOM. During the years, information technology has dramatically developed, new algorithmic methods evolved and the entire fields of electronic communication, machine automation, autonomous machines and process optimization developed. Consequently, today, APCOM is much more than a meeting of specialists in geostatistics and resource estimation: The APCOM has expanded to a conference covering all kinds of Information and Communication Technology in the mineral industry: Already in 2005 on the conference in Tuscon/AZ, the term "Mining Process Optimization" was presented as the next paradigm shift in mining after mechanization and automation, which marked another example of the continued innovative impact of the APCOM. Well ahead of the current discussions about "Digital Transformation".